Flat-roof phenomenon of dynamic equilibrium phase in the negative bias temperature instability effect on a power MOSFET - 张月 卓青青 刘红侠 马晓华 郝跃 (Chinese physics B, 2014)
The effect of the static negative bias temperature （NBT） stress on a p-channel power metal-oxide-semiconductor field-effect transistor （MOSFET） is investigated by experiment and simulation. The time evolution of the negative bias temperature instability （NBTI） degradation has the trend predicted by the reaction-diffusion （R-D） model but with an exaggerated time scale. The phenomena of the flat-roof section are observed under various stress conditions, which can be considered as the dynamic equilibrium phase in the R-D process. Based on the simulated results, the variation of the flat-roof section with the stress condition can be explained.